Tutorial action during the veterinary doctoral program at the Complutense University of Madrid, Spain - Fuertes-Recuero, Manuel; De Pablo-Moreno, Juan A.; Heras-Molina, Ana; Morón-Elorza, Pablo; Encinas Cerezo, Teresa (Frontiers in Veterinary Science, 2025)
The tutorial activity within doctoral programs is a fundamental process for the comprehensive training of the doctoral student, encompassing more than just direct thesis supervision. In the context of the Spanish regulations (Royal Decree [RD] 99/2011) and the policies of the Complutense University of Madrid (UCM), the tutor's role is distinct from that of the thesis supervisor. The tutor is responsible for guiding the doctoral student in developing general, transversal and specific competences in the technical-scientific, teaching and academic fields, while the thesis supervisor focuses solely on overseeing and guiding the research work. This study examines the tutor's role in the Veterinary Doctoral Program, based on an interpretation of the guidelines established at the UCM and the perceptions of both tutors and doctoral students. It aims to analyze shared expectations and responsibilities in the tutoring relationship, to explore whether tutors meet students' expectations, and to understand tutors' approaches to their work. The methodology used is based on the analysis of documented agreements between students, tutors and thesis supervisors, as well as institutional regulations. The study emphasizes that tutorial action should not only include support in the field of research, but also a broader education. This holistic formation integrates complementary scientific training (participation in courses and conferences), aiding the student in teaching activities (preparation of classes, seminars or lectures), or helping in management activities such as applying for projects or grants. The results obtained highlight the fact that the tutor in the Veterinary Doctoral Program should evaluate and guide the students' training activities on an annual basis, fostering an open feedback relationship that promotes intellectual development and formative metaknowledge. This study emphasizes that tutoring should cover four areas: the scientific area, the teaching area, the personal area and the academic management area. In conclusion, the tutorial process should be a co-responsibility action between tutors and doctoral students who collaborate effectively, understanding and fulfilling their roles. Aligned with the doctoral program's goals, it is essential to support the academic and professional integration of the doctoral student.